Double-row rotator cuff repair yields improved tendon structural integrity, but no difference in clinical outcomes compared with single-row and triple-row repair: a systematic review. Issue 5 (7th September 2017) - Rush, Lane N; Savoie, Felix Henry; Itoi, Eiji
Abstract : Importance: Techniques for arthroscopic rotator cuff repair are rapidly evolving. Single-row (SR) and double-row (DR) repair techniques have been well described, but recent studies have suggested the biomechanical superiority of transosseous-equivalent (TOE) DR repairs and triple-row (TR) repairs. However, there is conflicting literature regarding the clinical superiority of one technique over the other. Objective: To systematically review the best available evidence for arthroscopic repair of rotator cuff tears using SR, DR and TR techniques, and to identify predictors of patient functional outcomes and retear rates in each group. Evidence review: PubMed, Embase, Google Scholar and the Cochrane Database of Systematic Reviews were searched to identify all clinical papers describing arthroscopic repair of rotator cuffs using SR, DR or TR techniques. Findings: There were 10 papers that met our study criteria; they involved 580 patients. There was no significant difference in clinical outcomes between SR and DR repairs (p=0.57). Studies involving TR repairs were too underpowered to detect any difference in clinical outcomes between SR and DR repairs. The imaging confirmed retear rate of SR repairs was 30.3% (71/234), whereas DR repairs demonstrated a retear rate of 19.3% (41/212). The retear rate of TR repairs was 23.5% (8/34), but the low number of reported TR repairs did not allow us to make any conclusions regarding its superiority or inferiority compared with SR or DR. DR repairs demonstrated a statically significant decrease in retear rates compared with SR repairs (p=0.001). A subgroup analysis of retear rates in SR repairs versus TOE DR repairs demonstrated a trend towards improved structural integrity of the TOE DR repairs, but this was not statistically significant (p=0.07). Conclusions and relevance: There is no clear difference in clinical outcomes between SR, DR and TR techniques, but DR techniques demonstrate improved structural integrity at short-term follow-up. Level of evidence: IV.